Gender wage differentials in China's urban labour market - Meiyan Wang; Fang Cai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper describes and decomposes wage differences between female and male workers. The results indicate that females receive low wages because of unequal pay within sectors, and that the wage gap caused by the difference in sectoral attainment is small. The results also reveal that a lion's share of the wage differential between females and males is attributable to discrimination rather than to the human capital difference between the genders. Eliminating discriminations against females with a focus on intra-sectoral inequality is crucial for reducing female/male wage differentials.
Keywords: J16; J31; J71; 330; labour market; wage differentials; gender discrimination; Lohndifferenzierung; Geschlecht; Städtischer Arbeitsmarkt; China